Integrasi Media Digital Dalam Rencana Layanan Bk Komprehensif : Strategi Penguatan Perencanaan Karir Generasi Alpha - Azzahra, Ratu Fathimah; Prasetya, Akhmad Fajar (Jurnal Ilmu Bimbingan dan Konseling, 2025)
Alpha Generation students in boarding school environments require a unique career guidance approach due to their characteristics as digital natives with high visual expectations. This study aims to design a classical guidance model within the Comprehensive Guidance and Counseling (Comprehensive GC) framework by integrating innovative digital media. Using a library research method through the Google Scholar database, this study analyzes five key articles relevant to the development of digital media in guidance and counseling services. The findings indicate that: (1) gamification strategies and artificial intelligence (AI) are effective as curiosity triggers for students; (2) immersive media such as 360° videos are able to bridge the limitations of boarding school students’ physical access to the global industrial world; and (3) career identity personalization through creative design platforms such as Canva enhances students’ self-efficacy in STEM fields. The conclusion of this study emphasizes that the integration of technology in classical guidance services is not merely a supporting tool, but a central pillar in fostering students’ independent and adaptive career maturity in the era of Society 5.0.